KAJIAN IBADAH DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Shinta Haryani; Nurul Magfira; Windi Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The study of worship from the perspective of Islamic Religious Education plays a crucial role in shaping the character and spirituality of students. Worship is not only understood as a ritual activity, but also as an educational tool that instills the values ​​of faith, discipline, responsibility, and noble morals. This article aims to examine the concept of worship and its implementation in Islamic Religious Education. The research method used is a literature study with a descriptive-analytical approach through various literature sources, such as the Qur'an, hadith, books, and relevant scientific journals. The results of the study indicate that worship education plays a significant role in shaping the personality of religious and character-based students. The implementation of worship education can be done through habituation, teacher role models, strengthening spiritual values, and applying worship in daily life. In addition, worship education also serves as a means to increase students' awareness in practicing Islamic teachings comprehensively. Thus, the study of worship from the perspective of Islamic Religious Education can be the basis for creating a generation of faith, piety, and noble character in accordance with the goals of Islamic education.